Modulation of Host miRNAs by Intracellular Bacterial Pathogens - Das, Kishore; Garnica, Omar; Dhandayuthapani, Subramanian (Frontiers in Cellular and Infection Microbiology, 2016)
MicroRNAs (miRNAs) are short non-coding RNAs that regulate the expression of protein coding genes of viruses and eukaryotes at the post-transcriptional level. The eukaryotic genes regulated by miRNAs include those whose products are critical for biological processes such as cell proliferation, metabolic pathways, immune response, and development. It is now increasingly recognized that modulation of miRNAs associated with biological processes is one of the strategies adopted by bacterial pathogens to survive inside host cells. In this review, we present an overview of the recent findings on alterations of miRNAs in the host cells by facultative intracellular bacterial pathogens. In addition, we discuss how the altered miRNAs help in the survival of these pathogens in the intracellular environment.